Analysis of Learning Achievement Level Towards Implementation of Outcome-Based Education (OBE) in Geography Education Department - Lubis, Darwin Parlaungan; Rahmadi, M Taufik; Pratama, Alvin; Novira, Nina; Sintong, Mahara; Permana, Sendi; Suciani, Ayu (Tunas Geografi, 2024)
Rapid changes in the world of work due to globalization and the information technology revolution require an evaluation of the competencies needed considering the gap between educational outcomes and job market demands. Outcome-Based Education (OBE) is considered to be able to bridge this gap by focusing on learning outcomes that are relevant and in accordance with the needs of the world of work, replacing the teacher-centered teaching method that is still dominant. This study aims to analyze the implementation of OBE in the Department of Geography Education and evaluate the level of student learning achievement to meet professional demands in the field of geography. This research uses a quantitative descriptive method to describe the level of student learning achievement related to implementing Outcome-Based Education (OBE) in the Department of Geography Education, with a population of all students and samples taken using purposive sampling from the 2023 and 2024 classes. Data were collected through a closed questionnaire distributed via Google Forms, using a Likert scale from 1 to 5, and analyzed using descriptive statistics to calculate the percentage of respondents' answers and the average answer per item. The study's results showed that implementing Outcome Based Education (OBE) had a positive impact with an average student learning achievement reaching 73.8%. However, there are still shortcomings in mastery of technology and application of theory to real practice, which emphasizes the need to develop a more applicable curriculum. To improve these skills, it is recommended that universities integrate experiential learning methods such as internships and case studies and focus on curriculum evaluation that is integrated with practical experience.